Compassion—A key to innovation: What promotes and what prevents innovation in organizations? - Spännäri, Jenni; Juntunen, Elina; Pessi, Anne Birgitta; Ståhle, Pirjo (Frontiers in Psychology, 2023)
Innovation is crucial for the survival and wellbeing of organizations in volatile, rapidly changing societies. However, the role of profound human capability, compassion, and innovation has not been adequately investigated. This article sets out to explore the factors preventing and promoting innovation in organizations, asking how compassion is connected to these factors, and how compassion could boost innovation. We approach innovation as a complicated multilevel phenomenon, emerging from interactions between individuals and the work context. Our view of compassion includes both compassion and copassion—responding both to the suffering and joy of others. Our material was collected from nine focus group interviews, organized in Finland in 2017, in private, public, and third-sector organizations. The material was analyzed by two researchers, using an adapted grounded theory methodology. We found four core factors capable of either promoting or preventing innovation: (1) the strategy and structures of the organization, (2) resources, especially time, (3) working culture; and (4) the dynamics of interaction between individuals and the community. Our key conclusion, fruitful to theorizing both innovation and compassion, is that for innovation to flourish, compassion is to be cultivated throughout an organization. It is not a single variable or practice, and it is in many ways in a key position regarding innovation: the existence of it promotes innovation, but the lack of it prevents innovation. Thus, organizations aiming for innovation should seek multifaceted understanding and skills in compassion.